POLIMORFISME CYP2C19*2 TERHADAP AGREGASI PLATELET DAN KEJADIAN KARDIOVASKULAR PADA PASIEN PENYAKIT JANTUNG KORONER - Primanitha Ria Utami; Ike Dhiah Rochmawati; Selly Septi Fandinata (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2021)
Coronary Heart Disease (CHD) is a cardiovascular disease that can caused by the presence of coronary artery plaque blockage. Clopidogrel is one of antiplatelet therapy in CHD patients. CYP2C19 *2 polymorphisms can reduce the effectiveness of clopidogrel active metabolites. This research was conducted at RSUD Sidoarjo East Java from November to December 2017continued monitoring of cardiovascular events to March 2018. The research method used is a method Polymerase Chain Reaction (PCR) and the Light Transmittance Aggregometry (LTA) method for platelet aggregation measurement. From 25 sample inclusion,there are wild type alleles (bp values ​​around 120 bp; 1 patient), homozygous alleles (bp values ​​around 169 bp; 18 patients) and allele heterozygotes (bp values ​​around 120bp, 169bp; 6 patients). The most common type of polymorphism is allele homozygotes. There is one patient hyperaggregation and cardiovascular events after being monitored for 3 months. Analysis relationship between CYP2C19*2 genetic polymorphisms with platelet aggregation and cardiovascular events, using the kruskal wallis test. The result is no significant relationship between CYP2C19*2 polymorphisms with platelet aggregation (p=0.512), as well as cardiovascular events did not make any difference which is also significant (p=0.426). The results of the association of platelet aggregation with cardiovascular events showed significant differences (p=0.027).